Machine Learning for Enhanced Classification and Geospatial Distribution Analysis - Huang, Yuxi (Journal of Computer Technology and Applied Mathematics, 2025)
Combining geospatial analysis with machine learning creates a novel synergy beyond conventional approaches to comprehending our spatial surroundings. The ability of machine learning to recognize intricate patterns and connections within data has made it an indispensable instrument for geospatial analysts. This integration makes complex analyses of satellite imagery, climatic data, and geographic data possible, providing previously complex insights to obtain via manual or rule-based methods.